Teaching The Basics Of The Internet Of Things In A Distance Format (Eurasian Journal of Physics,Chemistry and Mathematics, 2024)
The article considers the experience of teaching the basics of the Internet of things in a distance format. The authors describe the chosen approach, the tools used, and the learning outcomes. Simulators such as Wokwi have been used to create virtual models of IoT devices and systems. The process of creating and debugging projects, as well as setting up automation scripts using the Google Colab cloud platform, is described. In conclusion, the authors summarize the results of the experiment and give recommendations for organizing IoT distance learning.